We agree about the metaneuropsychology of the ego (but not so much about the superego): A commentary on "Revisiting the left convexity hypothesis: Changes in the mental apparatus after left dorso-medial prefrontal damage" by Salas & Yuen. Issue 2 (2nd July 2016) - Solms, Mark
Abstract : I agree with the majority of the conclusions of Salas and Yuen concerning the metaneuropsychological functions of the left dorsolateral prefrontal convexity, which interpolates thinking (and therefore inner speech) between instinct and action. This is because I see the case described by them as supplementing rather than "revisiting" or "revising" our hypothesis regarding the left prefrontal convexity [Kaplan-Solms, K., & Solms, M. (2000). Clinical studies in neuro-psychoanalysis . London: Karnac], which concerned Broca's area rather than the left frontal convexity as a whole. I only find myself in disagreement with them when they describe the superego features of their case. I think the apparent superego deficits they describe are actually ego deficits, caused by changes in the ego's capacity to mediate superego demands. I elaborate on the dynamic localization of the superego, the supposed "head" of the ego, which is actually more deeply rooted in the mental apparatus than the bodily ego is. It is in fact extremely difficult to distinguish between ego and superego in topographic terms, as Freud acknowledged when he first introduced the concepts.